Mindfulness Practices to Support Art Educators: A Path to Preventing Burnout and Promoting Well-being - Fundaro, Daniela (The Canadian Art Teacher / Enseigner les arts au Canada, 2025)
This paper explores the role of mindfulness practices in mitigating challenges of burnout by fostering emotional regulation, creative engagement, and overall well-being. Drawing on the principles of Jon Kabat-Zinn’s (2003) Mindfulness-Based Stress Reduction (MBSR), Ellen Langer’s (2000) mindful learning, and my own experiences as an art educator, this article highlights practical mindfulness techniques that can be seamlessly integrated into the daily lives of art educators and teachers in general, helping to cultivate resilience, reduce stress, and rediscover their passion for teaching and creativity.